Phytodiversity of Species Used to Prepare "Tchonron" Sauce, A Cultural Dish of The Senoufo People, Northern Côte d’Ivoire - Tapily, Diallo Djeneba BAba; Yao, Konan; Olivier, Yao N’Guessan; Thierry, Koné Fankroma Martial (International Journal on Food, Agriculture and Natural Resources, 2024)
The Sénoufo, a people from the north of Côte d'Ivoire, are renowned for their consumption of leafy vegetables, particularly in the little-known ‘TCHONRON’ sauce. The aim of this study is to draw up a list of the leafy vegetables used in the preparation of this dish, in order to enhance their value and contribute to the sustainable management of these plant genetic resources. To this end, an ethnobotanical survey was carried out among 640 Senufo indigenous people, using a questionnaire. A total of 40 leafy vegetable species belonging to 28 genera and 20 families were identified. In fact, the most represented families are Solanaceae, Amaranthaceae and Asteraceae. The majority of these species are herbs (58%). Of these species, 25% are introduced (exotic); they are used as substitutes for wild leafy vegetables by the population in times of scarcity. On the other hand, introduced species contribute to the diversity of leafy vegetables used in the preparation of “TCHONRON” sauce. In addition, the leafy vegetables used to prepare this local product are dominated by Guinean-Congolese and Sudanese-Zambezian (GC-SZ) species, representing 55% of all species inventoried. This study reveals that the leafy vegetables used to prepare the “TCHONRON” sauce are diversified, and that the consumption of this sauce, a product of the Senoufo region, is not only cultural, but also contributes to the prevention of several diseases.